AGO2 Negatively Regulates Type I Interferon Signaling Pathway by Competition Binding IRF3 with CBP/p300 - Wang, Shengyu; Sun, Xin; Yi, Chenyang; Zhang, Dan; Lin, Xian; Sun, Xiaomei; Chen, Huanchun; Jin, Meilin (Frontiers in Cellular and Infection Microbiology, 2017)
Viral infection triggers a series of signaling cascades and host innate immune responses, including interferon (IFN) production, which depends on coordinated activity of multiple transcription factors. IFN regulatory factor 3 (IRF3) and transcriptional coactivator CREB binding protein (CBP) and/or p300 are core factors that participate in transcriptional complex formation in the nucleus. In general, cells balance the production of IFNs through suppressive and stimulative mechanisms, but viral infections can disrupt such equilibrium. This study determined that H5N1 viral infection reduced the distribution of human argonaute 2 (AGO2) in A549 cell nucleus. AGO2 did not block phosphorylation, nuclear translocation, and DNA binding ability of IRF3 but inhibited its association with CBP. Therefore, this newly revealed mechanism shows that cellular response leads to transfer of AGO2 from cell nucleus and promotes IFN-β expression to increase host survival during viral infection.